TINDAK PIDANA KORUPSI DITINJAU DARI PERSPEKTIF HUKUM ISLAM - Muhammad Husni Mubaraq (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2022)
The purpose of this research is to find out how Islam views corruption and how to eradicate corruption according to Islamic criminal law. The research method used in this research is normative juridical research and it can be concluded: 1. Corruption in Islam is an act of violating the Shari'a. Islamic law aims to realize the benefit of mankind with what is called maqashidussy syaria'ah. From the perspective of the wider context of Islamic teachings, the practice of corruption is an act that is contrary to the principles of justice, accountability, and responsibility. Corruption and all its negative impacts cause various distortions to the life of the State and society which can be categorized into acts of destruction on earth which are highly condemned by Allah swt. 2. Islamic Criminal Law places corruption in the category of jarimah takzir, takzir is a legal sanction that is imposed on a person who commits a crime or criminal act who commits violations both related to the rights of Allah swt and human rights, and these violations are not explicitly determined in the form of sanctions in the texts of the Qur'an and hadith. Takzir legal sanctions can be in the form of imprisonment, fines, inclusion in the list of disgraceful people, dismissal, and even the death penalty.